Assessment of Awareness and Knowledge of Medication Related Osteonecrosis of Jaw among Dental Students at a Tertiary Hospital in Eastern Nepal - Keshwar, Shashi; Sarraf, Deependra Prasad; Shrestha, Ashish; Jaisani, Mehul Rajesh; Shrestha, Sushmita (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: The medication related osteonecrosis of jaw (MRONJ) is caused by bisphosphonates, antiresoptive or antiangiogenic drugs. It is the basic requirement for dental students to know the drugs that causing MRONJ and its management. The study was conducted to assess awareness and knowledge of MRONJ among dental students and to compare the mean knowledge score. Methods: A cross-sectional study was conducted among dental students at College of Dental Surgery, B. P. Koirala institute of Health Sciences. A semi-structured questionnaires consisting of sociodemographic data and questions regarding awareness and knowledge of MRONJ. Descriptive statistics like mean, standard deviation, percentage and frequency were calculated. Students “t” test was used for statistical association between the variables at P-value of 0.05 using SPSS. Results: Out of 191, 63 (32.98%) students were aware that drugs other than bisphosphonates can also cause osteonecrosis of jaw while only 16.23% students were able to name such drugs. Majority of the students (91.62%) failed to give proper definition of the MRONJ. More than half of the students did not know that invasive dental treatments cannot be given to patients who are currently on oral or intravenous bisphosphonates. Majority (77.5%) of the students didn’t know the treatment guideline for MRONJ. Mean knowledge score of the students was 9.068±3.092. There was statistically significant association between the score and age, marital status and academic stream of the students (P-value <0.05). Conclusion: The study showed that students had average knowledge and awareness on MRONJ. The knowledge score was statistically associated with age, marital status and educational level. It suggests preeminent steps should be taken to educate future dental students about MRONJ at undergraduate and post graduate level of dentistry.